The Effect of Investor Status on Investors' Susceptibility to Earnings Fixation1. (21st July 2015) - Harris, Ling L.; Hobson, Jessen L.; Jackson, Kevin E.
Abstract: This study investigates whether an individual's status as a current or a prospective investor affects the investor's susceptibility to earnings fixation and proposes a mechanism to reduce earnings fixation. Our experimental results suggest that current investors are more susceptible to earnings fixation than prospective investors, and that current investors can reduce earnings fixation by explicitly forecasting future earnings as part of their evaluation process. We provide theory‐consistent evidence that current investors' prevention focus makes them elevate the importance of summary earnings in their evaluation of a company. However, after forecasting future earnings, current investors view summary earnings as only one of several similarly important evaluation inputs rather than as one substantially more important input (relative to its components). Our study contributes to research on earnings fixation and investor status. We also contribute to practice by documenting the moderating effect of investor status on earnings fixation and by identifying a simple mechanism that current investors can use to reduce their susceptibility to earnings fixation.